Yield components and seed attribute of nine varieties of open-pollinated chili. - Azmi, Chotimatul; Sembiring, Asma; Kurniawan, Helmi (Jurusan Agroteknologi, 2024)
Many studies related to chili varieties and productivity have been conducted. However, studies on the potential of seed production based on seed rendements to fulfil the need for chilli seeds are still limited. The study aimed to present rendement results, yield, and quality of the nine open-pollinated chilli seed varieties owned by the Indonesian Vegetable Research Institute (IVegRI), i.e. were Tanjung-2, Lembang 1, Ciko, Lingga, Kencana, Prima Agrihorti, Rabani Agrihorti, Carvi Agrihorti, and Branang, planted in a screen house. This study was conducted from January to December 2019. Cultivation techniques and seed certification followed the applicable Procedures. Data were analysed using descriptive methods. Observations were made on harvested fruits for yield and quality of seeds produced. The study revealed that Branang had the highest chili productivity (34.15 gm-2). Meanwhile, the highest seed rendement was Lembang 1 (5.48%). All varieties had good germination, namely above 75%. Based on the results, the breeders are expected to obtain information related to seed productivity from chili varieties owned by the Indonesian Vegetable Crops Research Institute (IVegRI). Penelitian terkait varietas dan produktivitas cabai telah banyak dilakukan. Akan tetapi, penelitian tentang potensi produksi benih berdasarkan rendemen benih untuk memenuhi kebutuhan benih cabai masih terbatas. Penelitian ini bertujuan untuk menyajikan hasil rendemen, daya hasil, dan mutu sembilan varietas benih cabai menyerbuk terbuka milik Balai Penelitian Tanaman Sayuran (Balitsa) yaitu Tanjung-2, Lembang 1, Ciko, Lingga, Kencana, Prima Agrihorti, Rabani Agrihorti, Carvi Agrihorti, dan Branang yang ditanam di rumah kaca. Penelitian ini dilaksanakan pada bulan Januari sampai dengan Desember 2019. Teknik budidaya dan sertifikasi benih mengikuti Prosedur yang berlaku. Data dianalisis dengan metode deskriptif. Pengamatan dilakukan terhadap buah yang dipanen untuk mengetahui daya hasil dan mutu benih yang dihasilkan. Hasil penelitian menunjukkan bahwa Branang memiliki produktivitas cabai tertinggi (34,15 gm-2). Sementara itu, rendemen benih tertinggi adalah Lembang 1 (5,48%). Semua varietas memiliki daya berkecambah yang baik, yaitu di atas 75%. Berdasarkan hasil penelitian ini diharapkan para pemulia tanaman dapat memperoleh informasi terkait produktivitas benih dari varietas cabai yang dimiliki Balai Penelitian Tanaman Sayuran (Balitsa).